Sporadic Creutzfeldt–Jakob disease with cerebellar ataxia at onset in the UK. Issue 11 (11th July 2006) - Cooper, S A; Murray, K L; Heath, C A; Will, R G; Knight, R S G
Abstract : Objective: To determine the frequency, in the UK, of sporadic Creutzfeldt–Jakob Disease (sCJD) with a cerebellar ataxic onset, and to describe the clinical features of the syndrome. Methods: A retrospective review of autopsy-proved cases of sCJD cases in the UK, 1990–2005, identifying those presenting with cerebellar features without early cognitive decline. Results: 29 of 618 (5%) patients with sCJD had an isolated cerebellar onset. Mean illness duration was 9 months. Subsequently, 21 (72%) developed myoclonus and 23 (79%) developed pyramidal features. Magnetic resonance imaging showed high signal in the basal ganglia in 11 of 14 (79%) patients. 7 of 15 (47%) patients were valine homozygotic at prion protein gene ( PRNP )-129. Only 8 (28%) cases were referred to the surveillance unit after death. Conclusion: A better definition of sCJD presenting with an isolated cerebellar syndrome might improve future case recognition and contribute to the determination of its cause.